2005
DOI: 10.1021/la048292v
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Rheology of CTAB/NaSal Aqueous Solutions:  Finite Extensibility of a Network of Wormlike Micelles

Abstract: The nonlinear rheology of aqueous solutions of cetyltrimethylammonium bromide (CTAB) and sodium salicylate (NaSal) was investigated. The concentration of CTAB was fixed at 0.1 mol L(-1), and the concentration of NaSal was varied from 0.07 to 0.4 mol L(-1). For all test solutions, dynamic moduli were described with the Maxwell model having a single relaxation time, tau. Time evolutions of the shear stress, sigma, and the first normal stress difference, N(1), after inception of the steady shear flow were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 35 publications
(77 reference statements)
3
58
0
Order By: Relevance
“…1,12) Concentration of CTAB, C D , and concentration of NaSal, C S , were fixed at C D = 0.1 M and C S = 0.1 M. All solutions were kept quiescently at room temperature prior to the tests for at least for two days for equilibration.…”
Section: Methodsmentioning
confidence: 99%
“…1,12) Concentration of CTAB, C D , and concentration of NaSal, C S , were fixed at C D = 0.1 M and C S = 0.1 M. All solutions were kept quiescently at room temperature prior to the tests for at least for two days for equilibration.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the shear thinning behavior is usually observed in entangled polymer systems. According to Inoue et al, 25,26) the strain-hardening behavior observed in the threadlike micellar system, CTAB:P(St/NaSS)/W, is attributed to the finite extensibility of the hybrid threadlike micelles forming fused temporal cross-links at entanglements as assumed in the phantom-crossing model. 13) Consequently, the relaxation mechanism for the hybrid threadlike micellar system is essentially explained with the phantom-crossing model as proposed in the previous study.…”
Section: Relaxation Mechanism For Hybrid Threadlike Micellar Systemmentioning
confidence: 99%
“…Inoue et al 25) have analyzed the strain-hardening behavior of the ordinary threadlike micellar system of CTAB:NaSal/W using a three-(freely jointed)-chain model. 28,29) In this model, threadlike micelles were regarded as non-gaussian freely jointed chains with a finite segment number giving finite …”
Section: Segment Size Of Hybrid Threadlike Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…These suggest that relaxation experiments at large strains belonging to the nonlinear regime 41,42) as the behavior of networks consisting of chainlike strands with finite extensibility 38) . From these, the essential characteristics of networks formed with threadlike micelles in the CTAB:NaSal/W system are possibly similar to those in the DO 3 B/C 10 system in aspects of both linear and nonlinear viscoelastic responses.…”
Section: Comparisons With Other Maxwell Elementmentioning
confidence: 99%